ANALISIS SEKTOR UNGGULAN KABUPATEN GAYO LUES - Irsan Pahalwan; Fakhruddin Fakhruddin (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract This study aims to determine the leading sectors of Gayo Lues Regency. The type of data used in this study is quantitative data because the data obtained is in the form of numbers. This study uses secondary data, data obtained from the Regional Statistics Agency (BPS). This study also draws data from the research literature related to this study. This study uses time series data from 2007 to 2017. The model used is the Location Qoutient (LQ) analysis model. There are 2 variables in the study, namely regency GRDP, Gayo Alas Plateau GRDP. Based on the results of the Location Quotient analysis which is the leading sector LQ 1 is the industrial and processing sector; financial sector, leasing and company services; electricity and drinking water sector; trade, hotel and restaurant sector; agricultural sector; and the building / construction sector.Keywords: economic growth, GDP, Production